Acceptance of the illness and the quality of life of patients with breast cancer - Kamińska, Marzena; Ciszewski, Tomasz; Bronikowska, Agnieszka; Ferańska, Maria; Pawlak-Warszawska, Agnieszka; Paśnik, Elwira (Polish Journal of Public Health, 2014)
Introduction. Breast cancer is the most frequent cancer diagnosed in women. Its treatment is a combined therapy and the sequence and time are established according to the accepted standards in Poland. Consequences posed by this disease include disorder in the physical, mental and social spheres in women. Adapting to cancer is very important for the process of treatment, and the acceptance of the disease is the determinant. Aim. The aim of the study was to determine and compare the degree of acceptance of the illness and the assessment of quality of life among breast cancer patients during cancer treatment. Material and methods. The survey included 85 ill people treated in a conserving way and 94 ill people treated by breast amputation. Patients after the surgical procedure were subjected to adjuvant treatment involving chemotherapy (90 women) and/or endocrine therapy (87 women). The study used standardized questionnaires EORTC (European Organisation for Research and Treatment of Cancer): QLQC-30 and the scale (AIS Approval IIIness Scale). Results. The highest level of acceptance of the disease, so the best ability to adapt to cancer have those women who have undergone radical mastectomy and adjuvant hormone therapy during the treatment. The lowest level of acceptance of the illness, expressed as a negative assessment was observed in women after BCT and during chemotherapy treatment. The use of the EORTC QLQC-30 to assess the overall health and quality of life of patients allowed us to capture statistically significant differences in the percentages stating good health, with the relatively highest negative response rates which were observed in the subgroups treated with chemotherapy and hormone therapy. With regard to the highest quality of life, the percentage of negative responses was observed in subgroups treated with the use of hormone therapy and after mastectomy. Conclusions. Good acceptance of the disease was obtained by women treated for breast cancer who have undergone mastectomy in the course of adjuvant endocrine therapy. The assessment of general health and quality of life was influenced by oncological treatment. Patients during chemotherapy and hormone therapy showed a negative impact of this form of treatment on overall well-being and functioning. Patients after mastectomy and during hormone therapy treatment showed a comparatively lower quality of life compared to a group of patients after BCT and during treatment with chemotherapy.